Līdzjūtība pret sevi un pašefektivitāte 18-25 gadus veciem jauniešiem - Bulmeistare, Arta (Latvijas Universitāte, 2016)
Pētījuma mērķis bija noskaidrot, kāda ir saistība starp līdzjūtību pret sevi un pašefektivitāti. Pētījumā tika izvirzīti divi jautājumi: vai pastāv saistība starp līdzjūtību pret sevi un pašefektivitāti; vai pastāv dzimumu atšķirības līdzjūtībā pret sevi un pašefektivitātē. Pētījumā piedalījās 125 respondenti. Sakarību noteikšanai tika izmantota Iejūtības pret sevi skala un Vispārējās pašefektivitātes aptauja. Pētījumā apstiprinājās, ka starp līdzjūtību pret sevi un pašefektivitāti pastāv statistiski nozīmīgas pozitīvās saistības. Tika atklāts, ka pastāv statistiski nozīmīgas dzimumu atšķirības līdzjūtībā pret sevi, savukārt dzimumu atšķirības pašefektivitātē nepastāv.

The aim of the study was to investigate, whether there is positive statistically significant connections between self-compassion and self-efficacy. The aim was also to answer to couple questions: what are the connections between self-compassion and self-efficacy, is there statistically significant gender differences in self-compassion and self-efficacy among women and men. In this study participated 125 respondents. For corelative and integroup research were used Self-compassion Scale and General Self-efficacy Scale. This study shows that there is significant positive connections between self-compassion and self-efficacy, also integroup study shows that there is statistically significant differences among women and men in self-compassion. The study did not show any significant gender differences in self-efficacy.
Self-compassion and Self-efficacy Among 18-25 Year Olds
Keywords: Psiholoģija; līdzjūtība pret sevi; pašefektivitāte; dzimums; psiholoģiskā funkcionēšana; psiholoģiskā labklājība